To find the zeros of f(x), follow the steps below.
Step 01: Use the quadratic formula.
For a quadratic equation y = ax² + bx + c, the zeros are:
![\begin{gathered} x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a} \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nk3bft20xor7rzbiz28ysgt23i1xfm7d29.png)
Step 02: Substitute the coefficients of f(x) in the quadratic formula.
For f(x) = x² + 8x + 12, the formula is:
![x=\frac{-8\pm\sqrt[]{8^2-4\cdot1\cdot12}}{2\cdot1}](https://img.qammunity.org/2023/formulas/mathematics/college/pnb79e3b4x1kzpcgl0wraszubn45mzav2x.png)
Step 03: Solve the quadratic formula.
![\begin{gathered} x=\frac{-8\pm\sqrt[]{64^{}-48}}{2} \\ x=\frac{-8\pm\sqrt[]{16}}{2} \\ x=(-8\pm4)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/c5918gtsy8bsoe71usq6wuw1lv9bq9appr.png)
And finally, find the zeros:
![\begin{gathered} x_1=(-8-4)/(2)=-(12)/(2)=-6 \\ x_2=(-8+4)/(2)=-(4)/(2)=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/h53f7un5c7d790bgvq0y5z0oyf45x3390w.png)
Answer: D) The zeros are -2 and -6.